Interactive Virtual Reality Video Walkthrough - Mohd Hanif, Mohd Ali (2007)
This research aims to builds a prototype that has Interactive Video and QuickTime Virtual Reality (QTVR) features into one program. Adobe Flash software has been used as the platform to develop this prototype because end user only needs to download small size of runtime file to play and interact with the program. Other than that, usability testing have been done on the prototype by using System Usability Scale (SUS) to test the prototype usability so that it is easier to use and closely fill user needs and requirements. As conclusions, this research successfully combines features of Interactive Video and QTVR in one prototype in Adobe Flash and successfully finished doing the usability testing.